Evaluation of the health and safety inspections state in the construction industry of Cyprus - Tantele, Elia A; Savva, Georgia C.; Votsis, Renos (My University, 2020)
Safe and healthy working conditions are a legal obligation in most countries. They can also serve as an investment in a healthy business that can lead to positive economic effects. Accidents at work and occupational diseases are neither predetermined nor unavoidable - they always have causes, which are preventable in many cases. International research on the return on investments in prevention proves that every euro invested in safety and health generates a potential benefit of more than two euros in positive economic effects. By building a strong prevention culture, these causes can be eliminated and work-related accidents and occupational diseases are prevented. In this paper, the Health and Safety (H&S) guidelines along their practical approaches of the Construction Sector in Cyprus are presented and evaluated. The applied methodology for the evaluation of the current H&S state is also presented. Through the evaluation, suggestions for future improvements are presented and discussed.
Keywords: Occupational hazards; Vision Zero